The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fpsyt.2023.1157790
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders in chronic pain and its neurochemical mechanisms: a narrative review

Lan Duo,
Xintong Yu,
Ruihan Hu
et al.

Abstract: Chronic pain (CP) is a prevalent problem, and more than half of patients with CP have sleep disorders. CP comorbidity with sleep disorders imposes immense suffering and seriously affects the patient’s quality of life, which is a challenging issue encountered by clinicians. Although the reciprocal interactions between pain and sleep have been studied to some degree, there is still a lack of awareness and comprehensive description of CP comorbidity with sleep disorders. In this narrative review article, we summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 114 publications
0
3
0
1
Order By: Relevance
“…(Hoegh, 2022;Wijma et al, 2016) Poor sleep has a direct correlation with chronic pain symptoms, therefore identifying and addressing sleep issues is an important component of pain care. (Duo et al, 2023;Siengsukon et al, 2017) Self-efficacy is an individual's belief that they can carry out certain tasks or behaviors; low self-efficacy is correlated with disability, pain intensity, and is a (Ferrari et al, 2019;Raman & Sharma, 2022). Mental imagery has been used for treatment of complex regional pain syndrome, phantom pain, and other chronic pain conditions, and has been found to alter pain sensations.…”
Section: Resultsmentioning
confidence: 99%
“…(Hoegh, 2022;Wijma et al, 2016) Poor sleep has a direct correlation with chronic pain symptoms, therefore identifying and addressing sleep issues is an important component of pain care. (Duo et al, 2023;Siengsukon et al, 2017) Self-efficacy is an individual's belief that they can carry out certain tasks or behaviors; low self-efficacy is correlated with disability, pain intensity, and is a (Ferrari et al, 2019;Raman & Sharma, 2022). Mental imagery has been used for treatment of complex regional pain syndrome, phantom pain, and other chronic pain conditions, and has been found to alter pain sensations.…”
Section: Resultsmentioning
confidence: 99%
“…У респондентів із високим рівнем фізичної активності спостерігався менший рівень суб'єктивного стресу (-0,76, p < 0.01). Сон і біль є важливими фізіологічними функціями, які взаємодіють одна з одною та впливають одна на одну в організмі людини [20]. Нами було виявлено значний зв'язок між порушенням сну у осіб молодого віку та інтенсивністю хронічного болю (0,63, p < 0.01).…”
Section: Resultsunclassified
“…Many studies, including ours, have shown that the use of single chemokine receptor antagonists (Scheme 1) can relieve pain of different etiologies, for example, the blockade of CCR1 (J113863) [7,8,17], CCR2 (RS504393) [6,187,188,220], CCR3 (SB328437) [7,21], CCR4 (C021) [28,64,65], CCR5 (maraviroc, AZD5672, TAK-220) [15,16,27,190], CXCR2 (NVP CXCR2 20, SB225002) [25,32,34,35,267,268,270], CXCR3 (NBI-74330, AMG487) [25,31,272], CXCR4 (AMD3100, AMD 3465) [43,273,274], and XCR1 (vMIP-II) [52,276]. It has been shown that some chemokines, e.g., CCL1 [5], CCL2 [12], CCL3 [17], CCL7 [12], CCL9 [17], and XCL1 [52], reduce the analgesic effect of opioids, and the use of neutralizing antibodies restores morphine and/or buprenorphine analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…The cause can be a metabolic, neurodegenerative, vascular, or autoimmune disease; a tumor; trauma; infection; or exposure to toxins. Neuropathic pain evokes severe suffering, disability, depression, and sleep disturbances [3][4][5], and its therapeutic management is challenging [6]. Recommended analgesics provide poor or unsatisfactory relief to patients [7].…”
Section: Chemokines and Neuropathic Painmentioning
confidence: 99%